Going More Open in Innovation: Does it Pay? - Fatur, Peter; Likar, Borut; Ropret, Marko (International Journal of Industrial Engineering and Management, 2010)
The research investigates into the relationship between the company’s innovation inputs and its performance. The research was carried out on the sample of 2503 Slovenian companies from manufacturing and selected service sectors. The results indicate a correlation between the revenues arising from innovations and the company’s performance in terms of the financial ratios, in particularly ROE and growth of revenues from sales. Furthermore, it is shown that the distribution of innovation expenditures is related to the company’s innovation performance. The financial inputs related to external sourcing of ideas and knowledge (open innovation) have a positive correlation with the innovation performance. Article history: Received (20.07.2010); Revised (30.09.2010); Accepted (10.10.2010)